DETERMINAN CASH HOLDING PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Meryna, Meryna; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of firm size, leverage, profitability, net working capital, and cash conversion cycle on cash holding in manufacturing companies listed on the Indonesian stock exchange. The research period is from 2017 to 2020. The study used a purposive sampling method and produced 260 research samples. The results of data processing with Eviews 12 student version lite show that the most suitable model used in predicting cash holding is the Random Effect Model (REM). Of all the independent variables, only three independent variables were found to affect cash holding, i.e. profitability, net working capital, and cash conversion cycle. The results showed that profitability and net working capital had a significant positive effect on cash holding while the cash conversion cycle had a significant negative effect.